2016
DOI: 10.1080/21645515.2015.1120393
|View full text |Cite
|
Sign up to set email alerts
|

Current status of new tuberculosis vaccine in children

Abstract: Pediatric tuberculosis contributes significantly to the burden of TB disease worldwide. In order to achieve the goal of eliminating TB by 2050, an effective TB vaccine is urgently needed to prevent TB transmission in children. BCG vaccination can protect children from the severe types of TB such as TB meningitis and miliary TB, while its efficacy against pediatric pulmonary TB ranged from no protection to very high protection. In recent decades, multiple new vaccine candidates have been developed, and shown en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…Although the Chinese government has strengthened TB control in minority areas over recent years achieving modest success, infantile TBM remains a neglected field [4][5]. WHO and numerous studies have reported that BCG vaccination can protect children from severe types of TB, such as TB meningitis and miliary TB [6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Chinese government has strengthened TB control in minority areas over recent years achieving modest success, infantile TBM remains a neglected field [4][5]. WHO and numerous studies have reported that BCG vaccination can protect children from severe types of TB, such as TB meningitis and miliary TB [6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Chinese government has strengthened TB control in minority areas over recent years with modest success, infantile TBM still remains a neglected field [4][5]. WHO and numerous studies have reported that BCG vaccination can protect children from the severe types of TB, such as TB meningitis and miliary TB [6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Chinese government has strengthened TB control in minority areas in recent years and achieved some success, childhood TBM still remains a neglected field [3][4]. WHO and numerous studies have been reported that BCG vaccination can protect children from the severe types of TB such as TB meningitis and miliary TB [5][6]. In many ethnic minority areas in southwest China, most residents live a nomadic lifestyle due to regional reasons, which makes the government's TB prevention and control work more difficult.…”
Section: Discussionmentioning
confidence: 99%